RULAL-commerce: using a board game to simulate the impacts of commercialization on land governance in Laos - CGIAR Research Program on Policies, Institutions, and Markets (2021)
The Rulal Commerce scenario is the latest addition in the Rulal boardgame series and was developed mid-2021.